Electromagnetic wave scattering by pyramid-shaped photonic crystal from resonant magnetodielectric spheres - Kozar, A. I. (Eskisehir Technical University, 2021)
The solution of the problem of scattering electromagnetic waves with a discrete convex polyhedron - a pyramid of resonant magnetodielectric spheres based on a complex rhombic crystal lattice is presented.
Keywords: electromagnetic waves; magnetodielectric spheres; crystal lattice